Perspectives on Adipose Tissue, Chagas Disease and Implications for the Metabolic Syndrome - Fnu Nagajyothi; Mahalia S. Desruisseaux; Linda A. Jelicks; Fabiana S. Machado; Streamson Chua; Philipp E. Scherer; Herbert B. Tanowitz (Interdisciplinary Perspectives on Infectious Diseases)
The contribution of adipose tissue an autocrine and endocrine organ in the pathogenesis of infectious disease and metabolic syndrome is gaining attention. Adipose tissue and adipocytes are one of the major targets of T. cruzi infection. Parasites are detected 300 days postinfection in adipose tissue. Infection of adipose tissue and cultured adipocytes triggered local expression of inflammatory mediators resulting in the upregulation of cytokine and chemokine levels. Adipose tissue obtained from infected mice display an increased infiltration of inflammatory cells. Adiponectin, an adipocyte specific protein, which exerts antiinflammatory effects, is reduced during the acute phase of infection. The antiinflammatory regulator peroxisome proliferator activated receptor-γ (PPAR-γ) is downregulated in infected cultured adipocytes and adipose tissue. T. cruzi infection is associated with an upregulation of signaling pathways such as MAPKs, Notch and cyclin D, and reduced caveolin-1 expression. Adiponectin null mice have a cardiomyopathy and thus we speculate that the T. cruzi-induced reduction in adiponectin contributes to the T. cruzi-induced cardiomyopathy. While T. cruzi infection causes hypoglycemia which correlates with mortality, hyperglycemia is associated with increased parasitemia and mortality. The T. cruzi-induced increase in macrophages in adipose tissue taken together with the reduction in adiponectin and the associated cardiomyopathy is reminiscent of the metabolic syndrome.